Valuasi Nilai Ekonomi dan Persepsi Pengunjung Taman Hutan Kota Bagan Pete Kota Jambi - Marwoto Marwoto; Suci Ratna Puri; Ade Adriadi (Fakultas Kehutanan Universitas Jambi, 2019)
This research was conducted in Bagan Pete Urban Forest. The purpose of this study was to obtain information about: (1) economic value of Bagan Pete Urban Forest, (2) demand equation model of Bagan Pete Urban Forest recreational benefits, 3) perceptions of visitors to Bagan Pete Urban Forest include education, convenience, and visitor satisfaction after coming to Bagan Pete Urban Forest Chart. The analytical method used is multiple linear regression analysis. The influence factors of frequency visits to Bagan Pete Urban Forest are travel costs (X1), monthly income (X2), age (X3), distance (X4), time spent on one visit (X5), long time knowing the Bagan Pete Urban Forest (X6), and gender (X7). The demand equation model obtained based on the travel cost method, namely: Y = 1.147 - 0.121X1 - 3.648X2 - 0.016X3 - 0.154X4 - 0.028X5 + 0.306X6 + 8.103X7, Y is the regression visit. The economic valuation of Bagan Pete Urban Forest in Jambi City is Rp 0.0071369 per year, and the surplus value of visitor customers is Rp 0.214107.